Generation and preclinical evaluation of a DENV-1/2 prM+E chimeric live attenuated vaccine candidate with enhanced prM cleavage - Keelapang P. (2014)
In the absence of a vaccine or sustainable vector control measures, illnesses caused by dengue virus infection remain an important public health problem in many tropical countries. During the export of dengue virus particles, furin-mediated cleavage of the prM envelope protein is usually incomplete, thus generating a mixture of immature, partially mature and mature extracellular particles. Variations in the arrangement and conformation of the envelope proteins among these particles may be associated with their different roles in shaping the antibody response. In an attempt to improve upon live, attenuated dengue vaccine approaches, a mutant chimeric virus, with enhanced prM cleavage, was generated by introducing a cleavage-enhancing substitution into a chimeric DENV-1/2 virus genome, encoding the prM. +. E sequence of a recent DENV-1 isolate under an attenuated DENV-2 genetic background. A modest increase in virus specific infectivity observed in the mutant chimeric virus affected neither the attenuation phenotype, when assessed in the suckling mouse neurovirulence model, nor multiplication in mosquitoes. The two chimeric viruses induced similar levels of anti-DENV-1 neutralizing antibody response in mice and rhesus macaques, but more efficient control of viremia during viral challenge was observed in macaques immunized with the mutant chimeric virus. These results indicate that the DENV-1/2 chimeric virus, with enhanced prM cleavage, could be useful as an alternative live, attenuated vaccine candidate for further tests in humans. © 2013 Elsevier Ltd.